Analisis Sanitasi Lingkungan dan Pengendalian Nyamuk di Kota Tarutung - Apriliani Lase; Angelia Putriana; Siti Aisyah; Apriliana Lase (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
Tarutung City, as the center of government and commerce in North Tapanuli Regency, faces environmental sanitation issues that contribute to the increase in mosquito populations. This study aims to analyze the condition of environmental sanitation and mosquito control efforts in Tarutung City. A descriptive-analytical approach was used to assess environmental cleanliness, the availability of sanitation facilities, and vector control programs implemented by the local government. The results of the study indicate that environmental sanitation in some areas remains inadequate, with many water storage sites found to be breeding grounds for Aedes aegypti mosquitoes, the primary cause of dengue fever. Control efforts, such as fogging and the elimination of mosquito breeding sites (PSN), have not been optimal due to the lack of community participation and awareness of the importance of maintaining environmental cleanliness. This study recommends enhancing public education programs, improving waste management, and conducting regular monitoring of high-risk areas to reduce mosquito populations and prevent disease spread. Strengthening cooperation between the government and the community is crucial to achieving a healthier environment free from mosquito threats